Identifikasi Respon Tanah terhadap Gelombang Gempa Bumi di Curup dan Implementasi Pembelajaran Fisika - Pio Kurnia Gusti; Muhammad Farid; Eko Swistoro; Irwan Koto (PendIPA Journal of Science Education, 2019)
ABSTRACT[Identification of Soil Response to Earthquake Waves in Curup and its Implementation on Physics Learning]. Scientific research has been conducted in the Curup in five districts namely Selupu Rejang, center Curup, eastern Curup, southern Curup and Curup city. Curup city is a mountainous area located in the earthquake belt. The aim of research was to determine the level of vulnerability of land in the Curup city and to explain the difference in student learning outcomes XI IPA 1 and XI IPA 2 after participating in learning by using learning model Problem Based Learning (PBL) and Conventional Methods on the material elasticity. Seismic susceptibility index data values obtained from field research using HVSR microseismic tools. Data management using DATAPRO software and GEOPSY software. The result of the highest level of susceptibility to the soil is 4.18 and is located at the maximum temperature of the soil. The results of educational research show that there are differences in student learning outcomes taught with PBL learning models and conventional methods. The experimental class learning outcomes have an average value of 80.70, while the control class has an average value of 73.20. Keywords: Vulnerability; earthquake; PBL model.(Received August 14 , 2018; Accepted January 10, 2019; Published February 27, 2019)  ABSTRAKPenelitian sains telah dilakukan di Daerah Curup di lima kecamatan yaitu Selupu Rejang, Curup Tengah, Curup Timur, Curup Selatan dan Curup Kota pada tanggal 07 Agustus 2016. Kota Curup merupakan daerah pegunungan yang terletak pada jalur gempa. Tujuan penelitian untuk mengetahui tingkat kerentanan tanah di kota Curup dan Untuk menjelaskan Perbedaan hasil belajar siswa kelas XI IPA 1 dan XI IPA 2 setelah mengikuti pembelajaran dengan menggunakan model pembelajaran Problem Based Learning (PBL) dan Metode Konvensional pada materi elastisitas. Data nilai indeks kerentanan seismik diperoleh dari penelitian lapangan dengan menggunakan alat mikroseismik HVSR. Pengelolahah data menggunakan software DATAPRO dan software GEOPSY. Hasil tingkat kerentanan tanah tertinggi mencapai 4,18 dan terletak pada kecamatan Selupu Rejang. Hasil penelitian pendidikan menunjukkan terdapat perbedaan hasil belajar siswa yang diajarkan dengan model pembelajaran PBL dan metode konvensional. Hasil belajar kelas eksperimen memiliki nilai rata-rata 80,70, sedangkan kelas kontrol memiliki nilai rata-rata 73,20.Kata kunci: Kerentanan; gempa bumi; model PBL.